(untitled) (Window of Public Health Journal, 2025)
Human movement activities, when implemented according to specific techniques, incorporate elements of play, evoke a sense of pleasure, and are often done in free time, resulting in a feeling of satisfaction. Humans themselves are living creatures whose physical activity is very high, often engaging in sports. This very high routine needs to be supported by a balanced psychological and physical condition of the body. Human movement activities, when implemented according to specific techniques, incorporate elements of play, evoke a sense of pleasure, and are often done in free time, resulting in a feeling of satisfaction. Humans themselves are living creatures whose physical activity is very high, which is often referred to as sport. This very high routine needs to be supported by a balanced psychological and physical condition of the body. The purpose of this study is to determine what descriptions support motivation and a person’s goals for doing running sports. This study employs a quantitative approach using descriptive methods to provide an in-depth description of running sports activities within the Indorunners community in Makassar City. The results of this study were obtained by distributing questionnaires to 50 respondents. This study was conducted in March 2025. The collected data were then processed using SPSS and presented in the form of frequency tables and distributions between variables. An overview of the running sports activities of the Indorunners community in Makassar city shows a high level of participation in running activities, although with significant variations in weekly running frequency among its members.